Pelanggaran Kedaulatan Wilayah Udara Kota Batam Indonesia Oleh Pesawat Boeing 737 Ethiopian Airline ETH3728 Tahun 2019 Berdasarkan Hukum Udara: Violation Of The Sovereignty Of The Airspace Of The City Of Batam By Boeing 737 Ethiopian Airline Eth3728 Based On Air Law - Kyla Rachmadyantira; Sugeng Supartono (Faculty of Law, Universitas Trisakti, 2025)
The case of violation of the sovereignty of Batam city airspace by Boeing 737 Ethiopian Airlines ETH3728 in 2019 is a serious violation of Indonesia's sovereignty. The problem of this research is: what are Indonesia's legal efforts in dealing with violations that occur and what are the factors that cause violations. The research method used, namely: normative juridical, descriptive, using secondary data, and data processing is done qualitatively. The results and the conclusion of this study indicate that Indonesia's legal efforts are carried out through the application of Law Number 43 of 2008 and in collaboration with ICAO. Then, the factors causing violations include air traffic density, lack of supervision, and weak international coordination. The research conclusion emphasizes the importance of strict law enforcement and effective international cooperation to maintain Indonesia's air sovereignty, as well as the need for increased surveillance and diplomacy to prevent future violations.